Left Lateral Prefrontal Activity Reflects a Change of Behavioral Tactics to Cope with a Given Rule: An fNIRS Study - Miura, Naoki; Shirasawa, Naoko; Kanoh, Shin’ichiro (Frontiers in Human Neuroscience, 2016)
Rules prescribe human behavior and our attempts to choose appropriate behavior under a given rule. Cognitive control, a mechanism to choose and evaluate actions under a rule, is required to determine the appropriate behavior within the limitations of that rule. Consequently, such cognitive control increases mental workload. However, the workload caused by a cognitive task might be different when an additional rule must be considered in choosing the action. The present study was a functional near-infrared spectroscopy (fNIRS) investigation of an experimental task, in which the difficulty of an operation and existence of an additional rule were manipulated to dissociate the influence of that additional rule on cognitive processing. Twenty healthy Japanese volunteers participated. The participants performed an experimental task, in which the player caught one of five colored balls from the upper part of a computer screen by operating a mouse. Four task conditions were prepared to manipulate the task difficulty, which was defined in terms of operational difficulty. In turn, operational difficulty was determined by the width of the playable space and the existence of an additional rule, which reduced the score when a red ball was not caught. The 52-channel fNIRS data were collected from the forehead. Two regions of interest (ROIs) associated with the bilateral lateral prefrontal cortices (LPFCs) were determined, and a three-way repeated-measures analysis of variance (ANOVA) was performed using the task-related signal changes from each ROI. The fNIRS results revealed that bilateral LPFCs showed large signal changes with the increase in mental workload. The ANOVA showed a significant interaction between the existence of an additional rule and the location of the ROIs; that is, the left lateral prefrontal area showed a significant increase in signal intensity when the additional rule existed, and the participant occasionally decided to avoid catching a ball to successfully catch the red-colored ball. Thus, activation of the left LPFC corresponded more closely to the increase in cognitive control underlying the behavioral change made to cope with the additional rule.